Computational Aspects of the Calculation of Isometry Groups in General Relativity - Roveda, Jose Arnaldo F. [UNESP]; Skea, James E. F.; Araujo, Marcelo E.; Roveda, Sandra R. M. M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 2009)
We describe the ideas behind the package 'isometry', implemented in Maple to calculate isometry groups of dimensions 2, 3 and 4 in General Relativity. The package extends the functionality of previous programs written to perform invariant classification of space-times in General Relativity. Programming solutions used to surmount problems encountered with the calculation of eigenvectors and the determination of the signs of expressions are described. We also show how the package can be used to find the Killing vectors of a space-time.